1976
DOI: 10.1007/bf01437750
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of beta decays of odd-A nuclides with 160<A<180

Abstract: A compilation is presented of experimental log J? values of allowed and first forbidden beta transitions in the region of strong nuclear deformation. Values of transitions between the same pairs of Nilsson states show considerable spreads which are not reduced by the application of calculated pairing reduction factors. E k. Beta Decay compiled logft (odd A, 160

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…But whether the metal activates them by complexing with the substrate PEP or by complexing with the enzyme is still a matter of debate. Several studies on PEPC from maize leaves concluded that the MgPEP complex is the true substrate of the enzyme [16,[26][27][28]. However, a more recent study claimed that PEPC binds the free species in an ordered fashion, with Mg# + binding before PEP [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But whether the metal activates them by complexing with the substrate PEP or by complexing with the enzyme is still a matter of debate. Several studies on PEPC from maize leaves concluded that the MgPEP complex is the true substrate of the enzyme [16,[26][27][28]. However, a more recent study claimed that PEPC binds the free species in an ordered fashion, with Mg# + binding before PEP [25].…”
Section: Discussionmentioning
confidence: 99%
“…No activation by free PEP ( f PEP) was detected in these studies. In contrast, from steady-state studies, also of the non-phosphorylated enzyme, in which the MgPEP complex was considered the variable substrate [16,[26][27][28], it was concluded that the binary MgPEP complex is the substrate of the reaction and that either free Mg# + ( f Mg# + ) [26] or f PEP [16] behaves as an activator. Thus the role that Mg# + , PEP or MgPEP has in the kinetics of the maize leaf PEPC-catalysed reaction is not clear at present.…”
Section: Introductionmentioning
confidence: 99%